2021
DOI: 10.1002/lio2.692
|View full text |Cite
|
Sign up to set email alerts
|

An equity‐based narrative review of barriers to timely postoperative radiation therapy for patients with head and neck squamous cell carcinoma

Abstract: Objectives: The majority of patients with head and neck squamous cell carcinoma (HNSCC) do not commence postoperative radiation treatment (PORT) within the recommended 6 weeks. We explore how delayed PORT affects survival outcomes, what factors are associated with delayed PORT initiation, and what interventions exist to reduce delays in PORT initiation. Methods: We conducted a PubMed search to identify articles discussing timely PORT for HNSCC. We performed a narrative review to assess survival outcomes of del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 69 publications
0
16
0
Order By: Relevance
“…Persistent associations with treatment delay included black race, public insurance, lower educational attainment, oral cavity tumor site, increased postoperative length of stay or unplanned readmissions, treatment at an academic center, and fragmented surgery and PORT at different locations. The parallels of our findings 5 years after the initial report underscores inadequate interventions to rectify this disparity despite expanding evidence dedicated to understanding patient and system‐level barriers to timely PORT 3–6 . Additionally, temporal trends are suggestive of worsening adherence over time.…”
Section: Discussionmentioning
confidence: 58%
See 2 more Smart Citations
“…Persistent associations with treatment delay included black race, public insurance, lower educational attainment, oral cavity tumor site, increased postoperative length of stay or unplanned readmissions, treatment at an academic center, and fragmented surgery and PORT at different locations. The parallels of our findings 5 years after the initial report underscores inadequate interventions to rectify this disparity despite expanding evidence dedicated to understanding patient and system‐level barriers to timely PORT 3–6 . Additionally, temporal trends are suggestive of worsening adherence over time.…”
Section: Discussionmentioning
confidence: 58%
“…A National Cancer Database (NCDB) analysis spanning 2006 through 2014 reported that greater than half of patients with HNSCC requiring PORT initiated treatment after 6 weeks from surgery 3 . Several subsequent publications attempt to further elucidate reasons for treatment delay and measures to implement targeted quality improvement interventions 4–6 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The interval between primary surgery and initiation of PORT is the primary driver of total treatment package time, affecting survival independent of diagnosis-to-treatment interval or duration of radiation therapy . Delays in PORT initiation disproportionately affect racial and ethnic minorities, those with Medicaid insurance, and those in medically underserved areas …”
Section: Introductionmentioning
confidence: 99%
“…There is some evidence that equity-based interventions can help reduce the achievement gap, but more research is needed to determine their precise effect and optimal implementation (Noyes et al, 2021). The purpose of this research is to investigate whether or not equity-based educational interventions are helpful in reducing the achievement gap, and if so, to what extent, and what kinds of obstacles and benefits schools may face when trying to implement such programs (Wald et al, 2019).…”
Section: Introductionmentioning
confidence: 99%